Effect of Scarification Position and Sulfuric Acid (H2so4) Concentration on Soursop Seed Viability (Annona muricata L.) - Siregar, Eka Pratika Duri; Nazimah, Nazimah; Safrizal, Safrizal; Nilahayati, Nilahayati; Khaidir, Khaidir (Journal of Tropical Horticulture, 2021)
Soursop is an annual plant that is rich in nutrients. The problem in soursop cultivation is that soursop has a hard seed coat, which causes the seeds to be impermeable to gases and air, inhibiting germination. Soursop seed dormancy can be broken by scarification and sulfuric acid immersion. This research aims to determine the effect of scarification position and sulfuric acid concentration on the viability of soursop seeds. The research used a completely randomized factorial pattern (CRD), which consisted of two factors with three replications. The first factor was the scarification position consisting of S0 (without scarification), S1 (base scarification), S2 (tip scarification) and S3 (middle scarification). The second factor was the sulfuric acid concentration consisting of K0 (control), K1 (10%), K2 (20%), and K3 (30%). The results showed an interaction between the treatment of scarification position and the concentration of sulfuric acid (c) on germination capacity and growth speed parameters. The combination of S0K1 (without scarification and 10% sulfuric acid) increased soursop seeds' germination and growth speed.